2016
DOI: 10.1002/msc.1146
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Reported Barriers to Healthcare Access for Rheumatoid Arthritis Patients in Rural and Northern Saskatchewan: A Mixed Methods Study

Abstract: Access to medical services is a concern for this population. Patients were dissatisfied with the waiting time for their first specialist appointment and with decreased access to allied health professionals. Patients travelling longer distances were more satisfied with their health care provider's care, suggesting that good patient-care giver relationships helped to ameliorate the difficulties of travelling to their appointments. Copyright © 2016 John Wiley & Sons, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 20 publications
0
18
0
Order By: Relevance
“…The majority of articles (33 of 43) addressed barriers to healthcare delivery and access that were related to healthcare professionals specifically [6,7,[10][11][12][13][14]17,[19][20][21][22][24][25][26][27][28][29][30][33][34][35][36][37][38]40,42,[44][45][46][47][48][49]. Practitioner-related barriers included staff shortages and high staff turnover, as well as lack of training, professional knowledge, skills and clinical expertise in treating specific medical conditions and working in areas that are distant from urban centres.…”
Section: Healthcare Provider-related Barriersmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of articles (33 of 43) addressed barriers to healthcare delivery and access that were related to healthcare professionals specifically [6,7,[10][11][12][13][14]17,[19][20][21][22][24][25][26][27][28][29][30][33][34][35][36][37][38]40,42,[44][45][46][47][48][49]. Practitioner-related barriers included staff shortages and high staff turnover, as well as lack of training, professional knowledge, skills and clinical expertise in treating specific medical conditions and working in areas that are distant from urban centres.…”
Section: Healthcare Provider-related Barriersmentioning
confidence: 99%
“…Many studies identified high staff turnover as a barrier to healthcare accessibility in the Circumpolar North [6,10,12,14,17,19,22,25,26,30,42,44,46]. Reasons identified as contributing to staff retention difficulties included the relative isolation of communities, being at a long distance from family, experiencing a lack of professional support and resources, and facing challenges in pursuing education for professional development [12,26,30,42].…”
Section: Healthcare Provider-related Barriersmentioning
confidence: 99%
“…The travelling required for accessing rheumatology follow‐up and care can be problematic for some people with RA living in these regions. In congruence with the 2002 Commission on Future of Health Care in Canada, which recognized geographic location as a determinant of health, people with RA in Northern Saskatchewan have identified barriers to healthcare access based on the location of residence (Nair, Schuler, Stewart, & Taylor‐Gjevre, ; Romanow, ). Key challenges identified include arranging transportation, environmental factors and road conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Key challenges identified include arranging transportation, environmental factors and road conditions. One‐third of people surveyed living in Northern Saskatchewan and outside of the major urban centre reported that they felt that their location of residence had a negative impact on their ability to access healthcare for RA (Nair et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…While other more economically developed countries are also facing a shortage of rheumatologists [ 25 , 26 ], the proportions are very different. The lack of specialized healthcare professionals in rheumatology leads to known barriers to bDMARD therapy in RA, such as long waiting time for medical visits and travel difficulties related to long distances to rheumatology clinical settings [ 27 , 28 ]. A study investigating patient-reported barriers to access bDMARD treatment in Romanian RA patients would assess the full extent of the issue.…”
Section: Discussionmentioning
confidence: 99%